The Carbon Kuznets Curve: A cloudy picture emitted by bad econometrics? - Martin Wagner (Institute for Advanced Studies (IHS), 2006)
In recent years many empirical studies of environmental Kuznets curves employing unit root and cointegration techniques have been conducted for both time series and panel data. When using such methods several issues arise: the effects of a short time dimension, in a panel context the effects of cross-sectional dependence, and the presence of nonlinear transformations of integrated variables. We discuss and illustrate how ignoring these problems and applying standard methods leads to questionable results. Using an estimation approach that addresses the second and third problem we find no evidence for an inverse Ushaped relationship between GDP and CO2 emissions.
Keywords: C12; C13; Q20; 330; Carbon Kuznets Curve; panel data; unit roots; cointegration; crosssectional dependence; nonlinear transformations of regressors